KONSEP PENDIDIKAN AGAMA ISLAM (PAI) BERBASIS PESANTREN DI LEMBAGA PENDIDIKAN UMUM - Sudadi Sudadi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2020)
This research starts from the general assumption that most of the Indonesian generation is dominated by Muslim communities who attend public schools rather than madrasa schools, whereas Islamic Religious Education (PAI) taught to students is more taught in madrasa schools. As a result, many Muslim students have a lack of understanding of religion and they do not understand perfectly (kaffah) about the values ​​contained therein. Islamic education in public schools such as elementary schools to senior high schools must receive development, modification, innovation and additional learning programs so that the integral objectives of Islamic education can be achieved properly. A more optimal learning system can be done by broadly modifying PAI subjects. Besides, pesantren-based education launched in public schools is to create students to have higher moral character. This study discusses the development and learning process of PAI in public schools that implement pesantren-based school programs. This study aims to describe the pesantren-based schools by describing the planning, implementation, and evaluation of the learning system. The analytical approach in this study is naturalistic by conducting a comprehensive and descriptive discussion on the focus of research in an integrated education system, with observation and interview methods, followed by testing the validity of data through frequent interactions with primary sources, conducting more diligent observation and conduction triangulation tests. Besides, this research uses descriptive analysis, cross-case analysis and comparative and inductive reasoning for the discussion and analysis of findings. The results of this study explain that the application of pesantren-based Islamic religious education in public schools has good grades for students because students can practice and explore religious knowledge as they should.